Progress in the Application of Animal-Derived Raw Materials in Health Foods in China - DUAN Hao, ZHOU Yaxi, ZHOU Shiqi, YAN Wenjie (Shipin Kexue, 2023)
Animal-derived raw materials are rich in various nutrients, especially the high level of protein, and have good application prospects in health foods and other fields. However, due to their special sources and processing methods, the requirements for the compliant use of animal-derived raw materials are stringent. Therefore, when animal-derived raw materials are used to produce health foods, great attention needs to be paid to relevant laws and regulations, processing methods and the requirements for their safe application. In recent years, a lot of new progress has been made in the studies on the bioactive ingredients and functions of animal-derived raw materials, but there are few reviews on the evidence for the compliance use of animal-derived raw materials in the production of health foods, the current status of the use of animal-derived raw materials in the production of health foods, and the health functions of animal-derived raw materials in functional foods. In this context, this paper presents the evidence for the compliance use of animal-derived raw materials in the production of health foods in China, and a statistical analysis of the current status of the use of animal-derived raw materials in the production of health foods using the national special food information query platform as a retrieval tool. We hope that this review will provide a useful reference for further mining, development and utilization of animal-derived raw materials.